EFFECTIVENESS OF VESTIBULAR STIMULATION IN CHILDREN WITH DEVELOPMENTAL COORDINATION DISORDER - SANKAR U, GANAPATHY; R, MONISHA; VALLABA DOSS, CHRISTOPHER AMALRAJ; RM, PALANIVEL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of this study were to find out the effects of vestibular stimulation in developmental coordination disorder (DCD) children. Methodology: Thirty children (n=30) were screened using the DCD questionnaire (DCDQ). After baseline screening among the 30 children, 15 were confirmed as suspects of DCD. Vestibular stimulation was given for all the 15 children. Results: It is revealed that the motor coordination was improved significantly in children with DCD. Conclusion: The present study concluded that vestibular stimulation is effective to enhance performance in tasks requiring motor coordination.